2019
DOI: 10.21203/rs.2.14125/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Influence of Job satisfaction, Resilience and Work engagement on Turnover Intention among Village Doctor in China:a cross-sectional study

Abstract: Background As the gatekeepers of rural residents ‘health, the team of village doctors plays a vital role in improving the health level of rural residents. However, a large number of village doctor’s turnover, or even dozens of them turnover collectively, threatening the stability of the village medical team. This research evaluated the influence of job satisfaction, resilience, work engagement on turnover intention of village doctor and explored the mediating role of resilience and work engagement between job … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…With the implementation of the new medical reform and the hierarchical medical system, the service mode of village doctors has changed from the passive “patient seeking medical treatment” to the active “health management service”, and from the combination of prevention and treatment to the comprehensive and whole-of-the-life-cycle health services [ 4 ]. The working mode of village doctors in village clinics is facing new and unprecedented challenges, they not only need to carry out daily medical treatment, but also public health, family doctor contract, family planning, chronic disease management and other services, which requires village doctors to update their knowledge and skills, and constantly improve the ability and quality of primary medical services [ 5 ]. However, in recent years, the situation of village doctors in China is facing severe challenges, including the difficulty of obtaining the qualification certificate of practicing doctors due to the low level of overall education, the poor level of wages and treatment, the difficulty of ensuring old-age insurance, the low social status, the difficulty of introducing young talents, and the overall instability of the ranks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the implementation of the new medical reform and the hierarchical medical system, the service mode of village doctors has changed from the passive “patient seeking medical treatment” to the active “health management service”, and from the combination of prevention and treatment to the comprehensive and whole-of-the-life-cycle health services [ 4 ]. The working mode of village doctors in village clinics is facing new and unprecedented challenges, they not only need to carry out daily medical treatment, but also public health, family doctor contract, family planning, chronic disease management and other services, which requires village doctors to update their knowledge and skills, and constantly improve the ability and quality of primary medical services [ 5 ]. However, in recent years, the situation of village doctors in China is facing severe challenges, including the difficulty of obtaining the qualification certificate of practicing doctors due to the low level of overall education, the poor level of wages and treatment, the difficulty of ensuring old-age insurance, the low social status, the difficulty of introducing young talents, and the overall instability of the ranks.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, there were two shocking and noticeable resignation incidents of village doctors, once 36 and once 28, in Henan province [ 5 ]. As a result, the total number of village doctors and the number of rural clinics in China is experiencing a sharp decline year by year.…”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that polychronicity significantly affected turnover intention. Many researchers have highlighted the effect of polychronicity on turnover intention in the hospitality industry (Asghar et al, 2021;Jang, 2008;Jang and George, 2012;Zhang, 2015). However, studies on this topic are scarce in the health-care sector.…”
Section: Discussionmentioning
confidence: 99%